2011
DOI: 10.1007/s12639-011-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture effects on the activity of three entomopathogenic nematodes (Steinernematidae and Heterorhabditidae) isolated from Meghalaya, India

Abstract: Entomopathogenic nematodes (EPNs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…There are certain species of Steinernema that can infect the host in soil with moisture level as low as 1% (Gungor et al, 2006) and 2% moisture level (Kung, 1990). In the present study, the highest numbers of established IJ were observed at 10% and 15% moisture level which is in close agreement with reports for H. indica strain T2 (Maketon et al, 2011), H. indica isolate from Meghalaya, India (Yadav, 2012) and H. bacteriophora (Susurluk et al, 2001). Further increase in water content resulted in decline in number of invading IJ indicating that higher moisture level can have detrimental effects on the control potential of EPN (Koppenhöfer et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are certain species of Steinernema that can infect the host in soil with moisture level as low as 1% (Gungor et al, 2006) and 2% moisture level (Kung, 1990). In the present study, the highest numbers of established IJ were observed at 10% and 15% moisture level which is in close agreement with reports for H. indica strain T2 (Maketon et al, 2011), H. indica isolate from Meghalaya, India (Yadav, 2012) and H. bacteriophora (Susurluk et al, 2001). Further increase in water content resulted in decline in number of invading IJ indicating that higher moisture level can have detrimental effects on the control potential of EPN (Koppenhöfer et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Ecological characterisation of H. indica isolated from different geographical regions have been reported previously (Ebssa et al, 2004;Iraki et al, 2000;Karunakar et al, 1999;Ma et al, 2013;Nguyen et al, 2006;Noosidum et al, 2010;Shamseldean et al, 1996;Shapiro-Ilan et al, 2005;Shapiro-Ilan et al, 2014;Shapiro-Ilan et al, 2009;Walia et al, 2008;Xu et al, 2010;Yadav, 2012). In the present study, we provide the ecology of the EPN H. indica isolated from the island of Viti Levu, Fiji.…”
supporting
confidence: 72%
“…The differences in the number of larvae emerging from one insect observed between the bioassays are confirmed by the other studies which demonstrated that the number of infective juveniles may fluctuate from few to few dozen thousand (Mason & Hominick 1995;Strong et al 1996). The differences in biology of nematodes isolated from the natural environment was also confirmed by the scientists conducting research on isolates of S. feltiae originating from Spain (Campos-Herrera et al 2006;Yadav & Lalramliana 2012).…”
Section: Resultssupporting
confidence: 52%
“…It is widely recognized now that the selection of a suitable EPN species as a biocontrol agent in a given geographical area requires adequate knowledge about the biology and ecology of the nematode. Information relating to the above three EPN isolates, such as the effects of soil moisture on the establishment and the effects of relative humidity on the emergence and reproduction were studied by Lalramliana and Yadav (2009) and Yadav and Lalramliana (2012c). Among other abiotic factors, the temperature is also considered as an important factor in determining the suitability of EPN as an appropriate biocontrol agent.…”
Section: Introductionmentioning
confidence: 99%